(untitled) (Research, Society and Development, 2025)
Pharmaceutical innovation is a fundamental process that involves the development, research and introduction of new drugs and therapies onto the market. This includes the discovery of new molecules, improvements in drug delivery technologies, enhancement of existing formulations and the search for new treatments for various diseases. One of the current challenges in this field is antimicrobial resistance, especially in relation to multi-resistant bacteria. To meet these challenges, innovation in the discovery and development of new drugs is essential. This is crucial for the development of new antibiotics and therapies capable of effectively combating multidrug-resistant bacteria. In addition, strategies to prevent and control antimicrobial resistance are key to ensuring the continued effectiveness of drugs over time. An important approach to gathering up -to-date information and developing better therapeutic options against multidrug-resistant bacteria is to search for the latest literature. In this context, a study was carried out to compile the most recent pharmaceutical innovations used to combat these infections by multidrug- resistant bacteria. The methodology used was a literature review of academic databases, with specific exclusion criteria to e nsure the relevance of the selected studies. This literature review covered several innovative techniques, such as computational modeling, technologies using nanocomposites, gold and silver nanoparticles, natural extracts, among others. These techniques represent promising approaches for the development of new antimicrobial treatments that can be effective against multidrug- resistant bacteria, complementing or replacing conventional treatments.